1983
DOI: 10.1210/endo-113-4-1325
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Liver Somatotropic and Lactogenic Binding Sites in Male and Female Rats*

Abstract: Developmental changes in liver somatotropic (GH) and lactogenic (PRL) binding sites were evaluated in male and female rats from birth to sexual maturity, and compared with growth velocity, plasma GH, PRL, testosterone, and estrogens. The affinity (Ka) and the concentration of these sites were determined from the analysis of equilibrium saturation curves with [125I]bovine GH and [125I]ovine PRL, incubated with liver homogenates. GH receptors rose from 6.4 fmol/mg protein at 8 days of age to 30.3 fmol/mg protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
45
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 40 publications
9
45
0
Order By: Relevance
“…Regulation of rat liver GH receptors by testosterone has not been documented, although it has been reported that females have more receptors than males [1,12,13]. Our studies confirm that testosterone decreases PRL receptors, and they establish a similar role for testosterone on GH binding in the livers of female rats.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Regulation of rat liver GH receptors by testosterone has not been documented, although it has been reported that females have more receptors than males [1,12,13]. Our studies confirm that testosterone decreases PRL receptors, and they establish a similar role for testosterone on GH binding in the livers of female rats.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to prolactin receptors, little is known about the regulation of G H receptors in rat liver by sex steroids, except that livers from female animals are known to have more receptor sites that those from males when measured in either whole hepatocytes [12] or microsomal membrane preparations [1,13].…”
mentioning
confidence: 99%
“…Newborn infants have undetectable levels of GH-BP [13,15,23], which is consistent with the absence of GH receptors in sheep [24] and rat [25] fetuses. In the developing human [13,15,23] and rat [4,25] both GH-receptors and GH-BP gradually increase, as is the case for the corresponding mRNAs [12].…”
supporting
confidence: 52%
“…In the developing human [13,15,23] and rat [4,25] both GH-receptors and GH-BP gradually increase, as is the case for the corresponding mRNAs [12]. GH-BP is low in patients with anorexia nervosa [26], consistent with the low hepatic GH receptors in undernourished rats [27].…”
mentioning
confidence: 82%
“…The increase of GHR mRNA in liver also paralleled the postnatal increase in G H binding sites on female liver membranes (17), suggesting a close relationship between GHR mRNA abundance and receptor protein concentrations. Similarly, the comparatively low GHR mRNA abundance observed in the other tissues is consistent with the low levels of G H binding reported for nonhepatic tissues (7).…”
Section: Methodsmentioning
confidence: 74%